PENERAPAN PROJECT BASED LEARNING PSYCHOLOGICAL ASSESSMENT TOOLS UNTUK MENINGKATKAN KOMPETENSI REKRUTMEN - Meita Santi Budiani; Ni Wayan Sukmawati Puspitadewi; Muhammad Syafiq; Satiningsih (Universitas Negeri Padang, 2023)
Psychology students are required to have competence in the field of psychological assessment. This competency includes administering tests, giving instructions, and scoring test results. However, the time provided by the campus for providing psychological assessment practices for students is not sufficient for developing these competencies, especially during a pandemic where lectures are conducted online. Lack of insight, knowledge, and skills regarding the use of psychological assessment tools is an obstacle for them to find work in the future. The goal to be achieved is to increase students' competence and insight in using psychological assessment tools. The method used is divided into three stages: online material debriefing, offline training, and practice. The first series of activities was attended by as many as 83 participants, while in the second activity, there were as many as 29 participants with psychology student or alumni status. The results of the community service activities that have been carried out are that students experience an increase in competence in psychological assessment tools. Keyword: competency, psychological assessment tools, project based learning